Viabilidade econômico-financeira: Implantação de ordenha robotizada em uma propriedade leiteira - Zanette, Moisés Ribeiro (2024)
The present study aims to analyze the economic viability of implementing robotic milking on a property located in the interior of the municipality of Capão Bonito do Sul- RS. The research used a quantitative approach, addressing information related to agricultural management, in an inductive analysis, aiming for an in-depth understanding of the results obtained. The data collection procedure used primary information, which was obtained directly from property owners through open informal interviews. Seeking to solve the problem of verifying the economic and financial viability of implementing robotic milking on a dairy property in the city of Capão Bonito do Sul. In conclusion, the economic and financial analysis demonstrated that the investment in robotic milking is a viable and profitable venture for agricultural property. Through strategic management and continuous investments in technology and training, the property will be able to achieve high levels of profitability combined with efficiency.